Fracture toughness and structural evolution in the TiAlN system upon annealing. Issue 1 (December 2017) - Bartosik, M.; Rumeau, C.; Hahn, R.; Zhang, Z.; Mayrhofer, P.
Abstract Hard coatings used to protect engineering components from external loads and harsh environments should ideally be strong and tough. Here we study the fracture toughness, K IC, of Ti1−x Alx N upon annealing by employing micro-fracture experiments on freestanding films. We found thatK IC increases by about 11% when annealing the samples at 900 °C, because the decomposition of the supersaturated matrix leads to the formation of nanometer-sized domains, precipitation of hexagonal-structured B4 AlN (with their significantly larger specific volume), formation of stacking faults, and nano-twins. In contrast, for TiN, where no decomposition processes and formation of nanometer-sized domains can be initiated by an annealing treatment, the fracture toughnessK IC remains roughly constant when annealed above the film deposition temperature. As the increase inK IC found for Ti1−x Alx N upon annealing is within statistical errors, we carried out complementary cube corner nanoindentation experiments, which clearly show reduced (or even impeded) crack formation for annealed Ti1−x Alx N as compared with their as-deposited counterpart. The ability of Ti1−x Alx N to maintain and even increase the fracture toughness up to high temperatures in combination with the concomitant age hardening effects and excellent oxidation resistance contributes to the success of this type of coatings.